Star Wars : Episode V, The Empire Strikes Back - Kershner, Irvin; Hamill, Mark; Ford, Harrison, 1942-; Fisher, Carrie (Beverly Hills, Calif. : Twentieth Century Fox Home Entertainment, 2006)
Luke Skywalker receives Jedi training from master Yoda while his friends are pursued by Darth Vader.
Originally released as a motion picture in 1980.
Features: includes the 1980 and 2004 versions, commentary George Lucas, Irvin Kershner, Ben Burtt, Lawrence Kasdan, Dennis Muren, and Carrie Fisher, "Easter egg" credit roll, X-Box playable game demo, Lego game trailer.
Mark Hamill, Harrison Ford, Carrie Fisher.
MPAA rating: PG.
DVD, Dolby digital 5.1 surround.
In English with optional English, French, or Spanish subtitles.
Keywords: Vader, Darth (Fictitious character) -- Drama; Star Wars films; Adventure films; Video recordings for the hearing impaired; Feature films; Science fiction films